Analisis Perumusan Tujuan Pembelajaran Pada Modul Ajar Bahasa Indonesia Kurikulum Merdeka Belajar - Faradiba, Alda; Perdana, Parrisca Indra (JOURNAL OF EDUCATION FOR ALL, 2024)
The purpose of this study is to find out how to formulate learning outcomes into learning objectives in the teaching module Indonesian grade IV teachers of SDN Kleyan 1 Socah. This research uses a descriptive qualitative approach to document studies. The data collection techniques used are interviews, observation and documentation. The results showed that there are still teachers at SDN Kleyan 1 who do not understand how to analyze learning outcomes to learning objectives and also the Flow of Learning Objectives When creating Teaching Modules so teachers are forced to start in order to complete class administration Download teaching modules on Google. Based on observations, interviews and documentation, the formulation of learning objectives has met existing competencies and content.